National health expenditures, 1990 - Levit, Katharine R. (CENTERS for MEDICARE & MEDICAID SERVICES, 1991)
During 1990, health expenditures as a share of gross national product rose to 12.2 percent, up from 11.6 percent in 1989. This dramatic increase is the second largest increase in the past three decades. The national health expenditure estimates presented in this article document rapidly rising health care costs and provide a context for understanding the health care financing crisis facing the Nation today. The 1990 national health expenditures incorporate the most recently available data. They differ from historical estimates presented in the preceding article. The length of time and complicated process of producing projections required use of 1989 national health expenditures—data available prior to the completion of the 1990 estimates presented here.